1986
DOI: 10.1111/j.1600-051x.1986.tb00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of a family manifesting premature exfoliation of deciduous teeth

Abstract: In a previous publication, we described the clinical and radiographic findings of a family in which the children manifested premature exfoliation of the deciduous teeth. We now report for the same family the results of extensive laboratory studies performed on blood and urine, analysis of periodontal microflora, and a family pedigree. We demonstrated the presence of putative periodontal pathogens in the subgingival microflora, elevated levels of serum antibodies reacting to Bacteroides gingivalis, Capnocytopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 28 publications
(22 reference statements)
1
38
0
1
Order By: Relevance
“…Periodontitis can be viewed as a disturbance of the microbial ecology resulting in an increase in the number of Gram-negative and anaerobic bacteria. Case reports have described an association between HP and periodontitis (Baab et al, , 1986Page and Baab, 1985;Watanabe et al, 1993). Baab et al (1985Baab et al ( , 1986 reported the presence of putative periodontal pathogens in the subgingival microflora and elevated levels of serum antibodies to the periodontal pathogen Porphyromonas gingivalis in HP patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Periodontitis can be viewed as a disturbance of the microbial ecology resulting in an increase in the number of Gram-negative and anaerobic bacteria. Case reports have described an association between HP and periodontitis (Baab et al, , 1986Page and Baab, 1985;Watanabe et al, 1993). Baab et al (1985Baab et al ( , 1986 reported the presence of putative periodontal pathogens in the subgingival microflora and elevated levels of serum antibodies to the periodontal pathogen Porphyromonas gingivalis in HP patients.…”
Section: Introductionmentioning
confidence: 97%
“…Case reports have described an association between HP and periodontitis (Baab et al, , 1986Page and Baab, 1985;Watanabe et al, 1993). Baab et al (1985Baab et al ( , 1986 reported the presence of putative periodontal pathogens in the subgingival microflora and elevated levels of serum antibodies to the periodontal pathogen Porphyromonas gingivalis in HP patients. Watanabe et al (1993) observed a severe periodontal destruction in the permanent dentition associated with serum antibodies to Porphyromonas gingivalis in a subject suffering from HP.…”
Section: Introductionmentioning
confidence: 97%
“…These children were assigned a diagnosis of hypophosphatasia on the basis of alkaline phosphatase and phosphoethanolamine levels. Baab et al (1986) noted that their data suggest an autosomal-dominant mode of transmission and suggest that hypophosphatasia might be considered in the etiology of some forms of pre-pubertal periodontitis and as a possible explanation for certain sitespecific periodontal destruction.…”
Section: (3) Genetic Defects Of Structural Componentsmentioning
confidence: 99%
“…The concomitant lack of or reduction in connective tissue attachment between the tooth and bone is thought to account for the early spontaneous exfoliation of the deciduous teeth. Baab et al (1986) described a family where all three children manifested premature exfoliation of the deciduous teeth similar to that seen in pre-pubertal periodontitis (Page et al, 1983). These children were assigned a diagnosis of hypophosphatasia on the basis of alkaline phosphatase and phosphoethanolamine levels.…”
Section: (3) Genetic Defects Of Structural Componentsmentioning
confidence: 99%
“…Evidence of skeletal defects is found in nearly all patients and includes hypomineralization, rachitic changes, and incomplete vertebrate ossification and occasionally lateral bony spurs on the ulnae and fibulae. [5]…”
Section: Introductionmentioning
confidence: 99%